Biocatalytic selective acylation of technical lignins: a new route for the design of new biobased additives for industrial formulations - Sarieddine, Aya; Hadjiefstathiou, Caroline; Majira, Amel; Pion, Florian; Ducrot, Paul-Henri (Frontiers in Chemistry, 2023)
In this paper, we describe the proof of concept of the potential use of a biocatalytic process for the functionalization of technical soda lignins from wheat straw through the selective acylation of primary hydroxy groups of lignin oligomers by acetate or hexanoate, thus preserving their free phenols unreacted. The selectivity and the efficiency of the method, although depending on the structural complexity of the starting material, have been proven on model compounds. Applied to the technical lignins, the acylation yield is only moderate, rather due to structural and chemical features induced by the industrial mode of preparation of the lignins than to the lack of efficiency of the method. However, most of the physicochemical properties of the lignins, including their antioxidant potential, are preserved, advocating the potential use of these modified lignins for industrial applications.